Enhancing Heat Tolerance of the Little Dogwood Cornus canadensis L. f. with Introduction of a Superoxide Reductase Gene from the Hyperthermophilic Archaeon Pyrococcus furiosus - Geng, Xing-Min; Liu, Xiang; Ji, Mikyoung; Hoffmann, William A.; Grunden, Amy; Xiang, Qiu-Yun J. (Frontiers in Plant Science, 2016)
Production of reactive oxygen species (ROS) can be accelerated under various biotic and abiotic stresses causing lipid peroxidation, protein degradation, enzyme inactivation, and DNA damage. Superoxide reductase (SOR) is a novel antioxidant enzyme from Pyrococcus furiosus and is employed by this anaerobic hyperthermophilic archaeon for efficient detoxification of ROS. In this study, SOR was introduced into a flowering plant Cornus canadensis to enhance its heat tolerance and reduce heat induced damage. A fusion construct of the SOR gene and Green Fluorescent Protein gene (GFP) was introduced into C. canadensis using Agrobacterium-mediated transformation. Heat tolerance of the GFP-SOR expressing transgenic plants was investigated by observing morphological symptoms of heat injury and by examining changes in photosynthesis, malondialdehyde (MDA), and proline levels in the plants. Our results indicate that the expression of the P. furiosus SOR gene in the transgenic plants alleviated lipid peroxidation of cell membranes and photoinhibition of PS II, and decreased the accumulation of proline at 40°C. After a series of exposures to increasing temperatures, the SOR transgenic plants remained healthy and green whereas most of the non-transgenic plants dried up and were unable to recover. While it had previously been reported that expression of SOR in Arabidopsis enhanced heat tolerance, this is the first report of the successful demonstration of improved heat tolerance in a non-model plant resulting from the introduction of P. furiosus SOR. The study demonstrates the potential of SOR for crop improvement and that inherent limitations of plant heat tolerance can be ameliorated with P. furiosus SOR.